Association of Blood Donor Sex and Prior Pregnancy With Mortality Among Red Blood Cell Transfusion Recipients - Edgren, Gustaf (JAMA, 2019)
IMPORTANCE: Evidence regarding associations of blood donor sex with mortality among red blood cell transfusion recipients is conflicting. OBJECTIVE: To study associations of donor sex and prior pregnancy with mortality of transfusion recipients. DESIGN, SETTING, AND PARTICIPANTS: Data from 3 retrospective cohorts of transfusion recipients (the Kaiser Permanente Northern California [KPNC] and Recipient Epidemiology and Donor Evaluation Study-III [REDS-III] databases of data from January 2013 to December 2016 and the Scandinavian Donations and Transfusions [SCANDAT] database with data from January 2003 to December 2012) were analyzed. Final dates of follow-up were December 31, 2016, for the KPNC and REDS-III cohorts and December 31, 2012, for the SCANDAT cohort. Stratified Cox regression models were used to estimate associations between donor exposure groups with risk of mortality, adjusting for the number of red blood cell unit transfusions. EXPOSURES: The number of transfused red blood cell units from female donors, previously pregnant donors, and sex-discordant donors (male donor and female recipient or female donor and male recipient). MAIN OUTCOMES AND MEASURES: In-hospital mortality. RESULTS: The study population included 34 662 patients (mean age, 69 years; 18 652 [54%] women) from the KPNC cohort, 93 724 patients (mean age, 61 years; 48 348 [52%] women) from the REDS-III cohort, and 918 996 patients (mean age, 72 years; 522 239 [57%] women) from the SCANDAT cohort. The median number of red blood cell transfusions per patient was 3 in the KPNC cohort, 2 in the REDS-III cohort, and 3 in the SCANDAT cohort. The percentage of transfusions from previously pregnant or parous donors was 9% in the KPNC cohort, 18% in the REDS-III cohort, and 25% in the SCANDAT cohort. The percentage of transfusions in the 3 cohorts from female donors ranged from 39% to 43%, from previously pregnant or parous donors ranged from 9% to 25%, and from sex-discordant donors ranged from 44% to 50%. There were 3217 in-hospital deaths in the KPNC cohort, 8519 in the REDS-III cohort, and 198 537 in the SCANDAT cohort. There were no statistically significant associations between any of the 3 donor exposures and in-hospital mortality in the 3 cohorts. Hazard ratios for in-hospital mortality per transfused unit from female donors were 0.99 (95% CI, 0.96-1.03) for the KPNC cohort, 1.00 (95% CI, 0.99-1.01) for the REDS-III cohort, and 1.00 (95% CI, 0.99-1.00) for the SCANDAT cohort. For units from previously pregnant or parous female donors, hazard ratios were 1.00 (95% CI, 1.00-1.01) for the KPNC cohort, 1.01 (95% CI, 0.98-1.03) for the REDS-III cohort, and 1.00 (95% CI, 1.00-1.01) for the SCANDAT cohort. For units from sex-discordant transfusions, hazard ratios were 1.02 (95% CI, 0.99-1.05) for the KPNC cohort, 0.99 (95% CI, 0.98-1.00) for the REDS-III cohort, and 1.00 (95% CI, 0.99-1.00) for the SCANDAT cohort. CONCLUSIONS AND RELEVANCE: Among red blood cell transfusion recipients, transfusions from female, previously pregnant, or sex-discordant donors were not significantly associated with increased mortality.